The Enigmatic N-Terminal Domain of Proglucagon; A Historical Perspective - Conlon, J. Michael (Frontiers in Endocrinology, 2021)
Enteroglucagon refers to the predominant peptide with glucagon-like immunoreactivity (GLI) that is released by the intestine into the circulation in response to nutrients. Development of a radioimmunoassay for glucagon revealed issues that were not apparent in applications of the insulin radioimmunoassay. The fact that some antisera raised against glucagon recognized glucagon-related peptides in extracts of both pancreas and gut whereas others recognized only components in the pancreas remained a mystery until it was realized that the “gut GLI cross-reactive” antisera were directed against an epitope in the N-terminal to central region of glucagon whereas the “pancreatic glucagon specific” antisera were directed against an epitope in the C-terminal region. Unlike the cross-reactive antisera, the glucagon specific antisera did not recognize components in which glucagon was extended from its C-terminus by additional amino acids. Initial attempts to purify enteroglucagon from porcine ileum led to the erroneous conclusion that enteroglucagon comprised 100 amino acids with an apparent molecular mass of 12,000 Da and was consequently given the name glicentin. Subsequent work established that the peptide constituted residues (1-69) of proglucagon (Mr 8128). In the 40 years since the structural characterization of glicentin, attempts to establish an unambiguous physiological function for enteroglucagon have not been successful. Unlike the oxyntomodulin domain at the C-terminus of enteroglucagon, the primary structure of the N-terminal domain (glicentin-related pancreatic peptide) has been poorly conserved among mammals. Consequently, most investigations of the bioactivity of porcine glicentin may have been carried out in inappropriate animal models. Enteroglucagon may simply represent an inactive peptide that ensures that the intestine does not release equimolar amounts of a hyperglycemic agent (glucagon) and a hypoglycemic agent (GLP-1) after ingestion of nutrients.